2014
DOI: 10.1073/pnas.1323529111
|View full text |Cite
|
Sign up to set email alerts
|

Flying Drosophila stabilize their vision-based velocity controller by sensing wind with their antennae

Abstract: Flies and other insects use vision to regulate their groundspeed in flight, enabling them to fly in varying wind conditions. Compared with mechanosensory modalities, however, vision requires a long processing delay (~100 ms) that might introduce instability if operated at high gain. Flies also sense air motion with their antennae, but how this is used in flight control is unknown. We manipulated the antennal function of fruit flies by ablating their aristae, forcing them to rely on vision alone to regulate gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 51 publications
5
135
2
Order By: Relevance
“…It is also important to appreciate that the stimuli most useful for performing systems identification are not necessarily good proxies for the perturbations that an animal experiences in nature. For example, whereas it has been informative to subject flies to brief perturbations in free flight [68,91], measurements of airflow in natural settings indicate that flies would rarely, if ever, experience perturbations at such short temporal scales [118][119][120]. They are much more likely to have to deal with large, long gusts and the design of their control system should be interpreted accordingly.…”
Section: Stability and Inner-loop Architecturementioning
confidence: 99%
“…It is also important to appreciate that the stimuli most useful for performing systems identification are not necessarily good proxies for the perturbations that an animal experiences in nature. For example, whereas it has been informative to subject flies to brief perturbations in free flight [68,91], measurements of airflow in natural settings indicate that flies would rarely, if ever, experience perturbations at such short temporal scales [118][119][120]. They are much more likely to have to deal with large, long gusts and the design of their control system should be interpreted accordingly.…”
Section: Stability and Inner-loop Architecturementioning
confidence: 99%
“…spider silk | airborne motion | flow sensing | acoustics | nanodimensional fiber M iniaturized flow sensing with high spatial and temporal resolution is crucial for numerous applications, such as high-resolution flow mapping (1), controlled microfluidic systems (2), unmanned microaerial vehicles (3)(4)(5), boundary-layer flow measurement (6), low-frequency sound-source localization (7), and directional hearing aids (8). It has important socioeconomic impacts involved with defense and civilian tasks, biomedical and healthcare, energy saving and noise reduction of aircraft, natural and man-made hazard monitoring and warning, etc (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…It has been shown that bees depend on optic flow to avoid obstacles [212,213]. Several studies have confirmed that many insects directly control flight speed in the presence of wind disturbance by using optic flow information [201,214,215]. The fact that the magnitude of the optic flow field is inversely proportional to the distance enables insects to spontaneously modulate the flight speed as a function of the distance to the ground or corridor in a strategic manner ( figure 16).…”
Section: (I) Compound Eyesmentioning
confidence: 97%
“…While vision can also provide flight speed feedback, its long latency may have adverse effects. Fuller et al [201] demonstrated that Drosophila rely on short delay response (approx. 20 ms) from antennae to augment the visual response that has the sensorimotor delay of 50-100 ms to actively regulate flight speed, resulting in a multi-model sensory feedback architecture.…”
Section: (Iv) Antennaementioning
confidence: 99%